Otimização do tempo e da quantidade de água no processo de produção do malte - Muzzolon, Eloiza (2020)
The malt production process, used for brewing beers, takes place in three distinct stages: maceration, germination and drying. The present study was planned considering the first two stages of the process, maceration and germination. In the first phase of the study, the time variation in the maceration process was evaluated, trying to get the ideal time for this phase, evaluating the responses of the parameters that determine the quality of the final malt for “BRS Cauê” barley. The second phase varied the time and amount of water in the germination stage using the Central Compound design with a 2² factorial scheme in which one factor is time (t) and the other was the amount of water (%). In this stage, two varieties of barley were used, one national (BRS Cauê) and one imported (Andrea) to compare their characteristics and quality. For both stages of the study, the quality of the barley was first assessed to sequentially assess the hydration of the grains with the analysis of the steeping index and degree of maceration, the quality of the malt of each barley is subsequently assessed. The results for the first stage of the study, where the maceration time was varied, showed no significant differences in the quality of the obtained malt. In the second stage of the study, which varied the time and the amount of water in the germination process, it was possible to verify a significant difference in the values of FAN for the BRS Cauê barley, whereas for Andrea barley the difference was perceived for diastatic power. Finally, it was found that, to improve the quality of the malt in the germination stage, it is necessary to increase the germination time and less water in this process.